Leadership of Kiai and Students' Obedience in Islamic Boarding School - Nur Chasanah (Resolusi: Jurnal Sosial Politik, 2021)
Islamic boarding schools (pesantren) are non-formal Islamic educational institutions where students (santri) live together in a cottage (dormitory) to study Islamic religious scholarship under the guidance of the caretaker of the cottage who is often referred to as a kiai. The pesantren, which from its inception, prioritized religious knowledge and pesantren culture, was easily able to apply the slogan sam'an watha'atan (submission and obedience) to the kiai which later became the principle of santri in everyday life. However, along with the development of increasingly modern pesantren, this principle has been displaced by various experiences and knowledge. The disobedience of santri to the kiai as a leader in the pesantren is caused by various factors, one of which is the perception of the santri towards the leadership of the kiai.